Simulation of High-Transmission Chiral Metamaterial with Impedance Matching to a Vacuum - 贾秀丽 孟庆鑫 王晓鸥 周忠祥 (Chinese physics letters, 2016)
For a previously simulated eight-broadband negative-refraction-index chiral metamaterial, we use S-parameter retrieval methods to determine the complex effective permittivity, permeability, and the impedance. We also calculate the figure of merit, which is defined as the ratio of the real and the imaginary refraction components, and compare it with those of fishnet metamaterials. The simulation results show that our chiral metamaterial exhibits high transmission and impedance matching to a vacuum. Also, we determine that the electric and magnetic dipoles of the surface plasmons play an important role in determining the nine resonance frequencies. Therefore, this investigation provides an experimental basis for developing metamaterial devices with multiple and broad resonance frequency bands.